PERBANDINGAN LEARNING JOURNAL DENGAN MIND MAP TERHADAP HASIL BELAJAR GEOGRAFI - Lamtiurma Ronasari Sinaga; Zulkarnain Zulkarnain; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2014)
This study was aimed to find out (1) the difference of students’ mean score in Pretest, (2) the difference of students’ mean score in Postest, (3) the difference of n-Gain learning result score which was taught by Learning Journal and Mind Map method. This study used quasi experiment research. The population was X grade students in which the samples were X.4 and X.8. The results showed that (1) there is no significant difference between students’ mean score in Pretest, (2) there is significant difference between students’ mean score in Postest, where Mind Map is higher, (3) there is difference of n-Gain learning result were which was taught by Learning Journal and Mind Map, where n-Gain of Mind Map is higher and included into moderate criteria.Penelitian ini bertujuan untuk mengetahui (1) perbedaan nilai rerata Pretest siswa, (2) perbedaan nilai rerata Posttest siswa, (3) perbedaan n-Gain hasil belajar siswa yang diajarkan dengan metode pembelajaran Learning Journal dengan Mind Map. Penelitian menggunakan metode eksperimen semu. Populasi dalam penelitian ini siswa kelas X dengan sampel kelas X.4 dan X.8. Hasil penelitian menunjukkan bahwa: (1) tidak ada perbedaan signifikan antara nilai rerata Pretest siswa, (2) ada perbedaan signifikan antara nilai rerata Posttest siswa, dimana rerata Mind Map lebih besar, (3) ada perbedaan n-Gain hasil belajar siswa yang diajarkan dengan metode pembelajaran Learning Journal dengan Mind Map, dimana n-Gain Mind Map lebih besar dan termasuk dalam kriteria sedang.Kata kunci: hasil belajar, learning journal, mind map.